1996
DOI: 10.1007/s002800050440
|View full text |Cite
|
Sign up to set email alerts
|

Optimal schedule for administering granulocyte colony-stimulating factor in chemotherapy-induced neutropenia in non-small-cell lung cancer

Abstract: A prospective randomized study was conducted to determine the optimal schedule of rhG-CSF (recombinant human granulocyte colony-stimulating factor). A group of 33 lung cancer patients treated with MVP therapy (mitomycin, vindesine, and cisplatin) were randomly assigned to three groups: an early prophylaxis group in which rhG-CSF was initiated on day 2 of the MVP cycle; a late prophylaxis group in which rhG-CSF was initiated on day 8; and a therapeutic group in which rhG-CFS was initiated after the onset of neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 14 publications
0
20
1
Order By: Relevance
“…Koumakis et al [9] have shown that starting G-CSF administration within 24-72 h after chemotherapy provides good neutrophil recovery and decreases the number of febrile episodes and the antibiotic use. However, in other studies G-CSF not given until more than 72 h after chemotherapy was associated with a similar pattern of hematologic recovery and meant the total dose of G-CSF administered was smaller [5,17]. In our study, with lenograstim started on day 5, the incidence of severe neutropenia and febrile episodes was slight and the cost of treatment was lower.…”
Section: Discussioncontrasting
confidence: 48%
“…Koumakis et al [9] have shown that starting G-CSF administration within 24-72 h after chemotherapy provides good neutrophil recovery and decreases the number of febrile episodes and the antibiotic use. However, in other studies G-CSF not given until more than 72 h after chemotherapy was associated with a similar pattern of hematologic recovery and meant the total dose of G-CSF administered was smaller [5,17]. In our study, with lenograstim started on day 5, the incidence of severe neutropenia and febrile episodes was slight and the cost of treatment was lower.…”
Section: Discussioncontrasting
confidence: 48%
“…Consequently, "rules of thumb" or more sophisticated methods of determination of the most promising protocols should be applied. "Rules of thumb" appear to fail in such a question as whether or not and by how long to delay the initiation of G-CSF support post-chemotherapy, leading to controversial results [5], [11], [19], [21]. In this work we applied a physiologically-based mathematical model of human granulopoiesis [20] in conjunction with doxurubicin PK/PD model in order to evaluate improved protocols of chemotherapeutic and myelo-supportive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, the latter tools falls short of clarifying which schedule of G-CSF is optimal with respect to chemotherapeutic drugs. This question is evaluated in costly clinical trials by an inefficient trial-and-error method, which lead to controversial results [5], [11], [19], [21]. It should be noted that G-CSF can cause unpleasant side effects such as bone pain.…”
Section: Introductionmentioning
confidence: 99%
“…First, a double-blind RCT [52] comparing GM-CSF with placebo in 60 patients; second, a threearm RCT [53] using prophylactic G-CSF in two arms and therapeutic G-CSF in the third arm, in 33 non-small lung cancer patients; and last, a RCT [54] comparing G-CSF with placebo in 138 patients. Overall, these small RCTs showed a decreased duration of neutropenia in the CSF arms, but failed to show other clinical benefi ts.…”
Section: Use Of Csf In Afebrile Neutropeniamentioning
confidence: 99%